PARAMETER GENETIK AYAM KAMPUNG DI KECAMATAN SIGI BIROMARU - Awaluddin, Awaluddin (AgriSains, 2012)
This study aims to know the heritability of body weight of age 1 to 12 weeks and the correlation coefficient of estimate breeding value of kampung chicken in Sigi Biromaru District. This study uses six males and 18 females as males and yearling. While technically a fertilisation using the natural way. The research data obtained from 121 of the tail, which consisted of 37 males and 84 females. Data were analyzed by using the VCE 6 (Groneveld, 2008), PEST (Groneveld, 1999), and SAS 9 using univariate  Animal  Models. The results of this study have (1) The heritability of body weight  from week 1 to week 12 ranged from 0.448 ± 0.076 to 0.500 ± 0.489 and (2) The correlation coefficient of body weight breeding value of 1 to 12 weeks of age in chickens ranged from 0.2019 between the age of 10 weeks to the age of one week, until 0.9217 at coefficient correlation between the age ​​10 weeks of age to the age of 9 weeks. Key words : Estimate breeding value, heritability.